Plasma shielding removes prior magnetization record from impacted rocks near Santa Fe, New Mexico - Kletetschka, Gunther; Kavkova, Radana; Ucar, Hakan (Scientific reports, 2021)
The shock exposure of the Santa Fe's impact structure in New Mexico is evidenced by large human-size shatter cones. We discovered a new magnetic mechanism that allows a magnetic detection of plasma's presence during the impact processes. Rock fragments from the impactites were once magnetized by a geomagnetic field. Our novel approach, based on Neel's theory, revealed more than an order of magnitude lower magnetizations in the rocks that were exposed to the shockwave. Here we present a support for a newly proposed mechanism where the shock wave appearance can generate magnetic shielding that allow keeping the magnetic grains in a superparamagnetic-like state shortly after the shock's exposure, and leaves the individual magnetized grains in random orientations, significantly lowering the overall magnetic intensity. Our data not only clarify how an impact process allows for a reduction of magnetic paleointensity but also inspire a new direction of effort to study impact sites, using paleointensity reduction as a new impact proxy.